Anodized titanium material and method for manufacturing the same
By forming a porous first anodized titanium layer and a second anodized titanium layer on the surface of the titanium base material, combined with the optimized electrolysis process, the problem of insufficient voltage resistance of the anodized titanium layer in the prior art is solved, and an anodized titanium material with high voltage resistance and high performance is achieved.
Patent Information
- Application Number
- CN201980052408.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-08-10
- Filing Date
- 2019-08-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2039-08-08
AI Technical Summary
It is difficult to form an anodic titanium oxide layer with high voltage resistance and an insulating layer for the electrostatic chuck of a plasma etching device.
By forming a porous first anodized titanium oxide layer on the surface of the titanium base material and further forming a second anodized titanium oxide layer under appropriate conditions, the composition and flow rate of the electrolyte are controlled, and the electrolysis process is optimized to improve the voltage resistance of the anodized titanium oxide layer.
The high voltage withstandability of the anodic titanium layer is achieved, and is suitable for use in plasma etching devices, avoiding insulation breakdown, and improving the overall performance of the electrostatic chuck.
Smart Images

Figure CN112585302B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an anodized titanium material and a method for manufacturing the same, and more particularly to an anodized titanium material having improved voltage resistance and being preferably used in, for example, an electrostatic chuck of a plasma etching device. Background Art
[0002] As an etching method for manufacturing semiconductor elements, plasma etching is known. In the plasma etching method, an etching gas is plasmatized in a vacuum chamber, and the semiconductor substrate is etched using ions and / or radicals generated by the plasmatization. The plasma etching device comprises: a vacuum chamber; a support table (susceptor), which is arranged in the vacuum chamber and carries the semiconductor substrate; and an upper electrode, which is arranged in the vacuum chamber opposite to the susceptor. The susceptor comprises a lower electrode. In addition, the upper electrode comprises a hole (gas introduction hole) for introducing the etching gas into the vacuum chamber. When plasma etching of the semiconductor substrate is performed, the etching gas is introduced into the vacuum chamber from the gas introduction hole while the semiconductor substrate is held on the susceptor, and plasma is generated by applying a high-frequency voltage between the lower electrode and the upper electrode.
[0003] In order to continuously hold the semiconductor substrate on the base during plasma etching, the base is provided with an electrostatic chuck. Generally, the electrostatic chuck includes an electrode and a dielectric layer (insulating layer) disposed on the upper side of the electrode, a semiconductor substrate is placed on the dielectric layer, and the semiconductor substrate is adsorbed and held on the electrostatic chuck by applying a predetermined DC voltage to the electrode. For example, in a Coulomb force type electrostatic chuck, the semiconductor substrate generates electrostatic induction or dielectric polarization relative to the charge applied to the electrode, thereby being charged, and an adsorption force (Coulomb force) is generated between the charge of the electrode and the charge of the semiconductor substrate. In addition, for example, in a Johnson-Rahbek force type electrostatic chuck, the charge applied to the electrode moves to the outermost surface of the dielectric layer through the dielectric layer, and the semiconductor substrate generates electrostatic induction or dielectric polarization relative to the charge, thereby being charged, and an adsorption force (Johnson-Rahbek force) is generated between the charge of the electrostatic chuck and the charge of the semiconductor substrate.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-136350
[0007] Patent Document 2: Japanese Patent Application Publication No. 2008-066707
[0008] Patent Document 3: Japanese Patent Application Publication No. 2014-053481
[0009] Non-patent literature
[0010] Non-patent literature 1: Albu, SP; Ghicov, A.; Macak, JM; and Schmuki, P., Phys. Stat. Sol. (RRL) 1, No. 2, R65-R67 (2007).
[0011] Non-patent document 2: Ghicov, A.; and Schmuki, P., Chem. Commun., 2009, 2791-2808. Summary of the invention
[0012] Problems to be solved by the invention
[0013] The electrostatic chuck used in the plasma etching device is required to have high voltage resistance, that is, the dielectric layer does not undergo insulation breakdown. As the material of the insulating layer (dielectric layer) of the electrostatic chuck, aluminum oxide (Al2O3) is known to be used. When aluminum oxide is used for the insulating layer, aluminum is usually used as the electrode and substrate below it, but there is a large difference in the thermal expansion coefficient between aluminum oxide and aluminum. Therefore, if the electrode temperature rises, a large stress is applied to the insulating layer due to the difference in thermal expansion coefficient between aluminum oxide and aluminum, and cracks are easily generated in the insulating layer.
[0014] As an alternative material system with a small difference in thermal expansion coefficient between the oxide layer and the base material, a titanium oxide / titanium system can be considered. In order to improve the voltage resistance of the insulating layer, the insulating layer needs to have sufficient uniformity and layer thickness. In addition, in order to obtain the surface smoothness required for the electrostatic chuck, the uniformity of the insulating layer is also important. As a method for forming a titanium oxide layer with high uniformity, titanium anodization is known. However, it is extremely difficult to form an anodized titanium layer with sufficient voltage resistance as an insulating layer of an electrostatic chuck for plasma etching, and no such example has been reported so far. In non-patent document 1, it is recorded that a layer with a thickness of 250μm (i.e., an anodized titanium layer) composed of TiO2 nanotubes self-organized into hexagons by anodization of titanium is grown, but the result of additional experiments conducted by the inventors is that under the conditions disclosed in non-patent document 1, an anodized titanium layer with a thickness of more than 20μm cannot even be obtained.
[0015] The problem of the present invention is to provide an anodized titanium material having the improved voltage resistance mentioned above. In addition, a method for manufacturing the anodized titanium material is provided. In addition, an electrostatic chuck for a plasma etching device having the anodized titanium material is provided. In addition, a cooling plate for a plasma etching device having the anodized titanium material is provided. In addition, a showerhead for a plasma etching device having the anodized titanium material is provided.
[0016] Solutions for solving problems
[0017] The first scheme of the present invention is an anodized titanium material, characterized in that it comprises: a titanium base material; and an anodized titanium layer provided on the surface of the titanium base material, the anodized titanium layer comprising a porous first anodized titanium layer, the anodized titanium layer having a withstand voltage of 500V or more at 25°C, a Vickers hardness of 200 or more, a film thickness of 20 μm or more and less than 80 μm, a surface arithmetic mean roughness Ra of less than 1.6 μm, a surface maximum height roughness Rz of less than 6.3 μm, and no pore cross-section having a shape that can contain a circle with a diameter of 0.5 μm or more is observed in any of the cross-section and the surface perpendicular to the thickness direction of the first anodized titanium layer.
[0018] In the present invention, the withstand voltage of the anodized titanium layer refers to the withstand voltage measured as the last applied voltage without insulation breakdown of the anodized titanium layer, while boosting the DC voltage between the base material and the surface of the anodized titanium layer until insulation breakdown occurs in the anodized titanium layer. It should be noted that the withstand voltage measured by this method is roughly consistent with the withstand voltage measured as the voltage at the time point when insulation breakdown occurs in the anodized titanium layer at the same temperature, when an AC voltage boosted at a certain speed is applied between the base material and the surface of the anodized titanium layer in accordance with JIS H8687. In addition, the arithmetic mean roughness Ra and the maximum height roughness Rz of the surface refer to the arithmetic mean roughness and the maximum height roughness specified in JIS B0601, respectively.
[0019] In the present invention, the film thickness of the anodized titanium layer can be measured by an eddy current film thickness meter (for example, MP2 / O model manufactured by Helmut Fischer, etc.).
[0020] In addition, "no pore cross-section having a shape that can contain a circle with a diameter of 0.5 μm or more was observed in any of the cross-section and the surface perpendicular to the thickness direction of the first anodized titanium layer" can be judged as follows: no pore cross-section (opening) having a shape that can contain a circle with a diameter of 0.5 μm or more was observed in any of the scanning electron microscope (SEM) images of the surface of the anodized titanium layer of the anodized titanium material and the SEM images of the surface after the anodized titanium layer was polished. The conditions of the SEM observation can be set, for example, to acceleration voltage: 5.0 kV, detection mode: reflected electron detection, magnification: 10,000 times. It should be noted that the "pore cross-section" in the SEM image of the surface of the anodized titanium layer is synonymous with the "opening of the pore".
[0021] In the first aspect of the present invention, it is preferred that the first anodized titanium oxide layer include a plurality of tubular pores extending in a direction intersecting a surface of the anodized titanium oxide layer.
[0022] In the first aspect of the present invention, it is preferred that the withstand voltage of the anodized titanium layer at 150°C is higher than the withstand voltage at 25°C.
[0023] In the first embodiment of the present invention, preferably, the anodized titanium layer further includes a second anodized titanium layer disposed between the titanium matrix and the first anodized titanium layer, and the fluorine content (unit: atomic %) of the second anodized titanium layer is lower than the fluorine content (unit: atomic %) of the first anodized titanium layer.
[0024] In the present invention, the fluorine content (unit: atomic %) of the first and second anodized titanium oxide layers can be measured by energy dispersive X-ray spectroscopy (EDS). The EDS measurement conditions when measuring the fluorine content of each anodized titanium oxide layer can be set to, for example, an accelerating voltage of 15.0 kV.
[0025] The second embodiment of the present invention is an electrostatic chuck for a plasma etching device, which is an electrostatic chuck for a plasma etching device. The electrostatic chuck for a plasma etching device comprises the anodized titanium material of the first embodiment of the present invention, and the anodized titanium layer is arranged on the outermost layer of the electrostatic chuck and is exposed to the plasma atmosphere.
[0026] The third scheme of the present invention is a cooling plate for a plasma etching device, which is a cooling plate for a plasma etching device, and the cooling plate for a plasma etching device comprises: the anodized titanium material of the first scheme of the present invention; and a refrigerant flow path, which is arranged inside the cooling plate to allow the refrigerant to circulate, and the anodized titanium layer is arranged on the outermost surface of the cooling plate.
[0027] The fourth scheme of the present invention is a nozzle for a plasma etching device, which is a nozzle for a plasma etching device, and the nozzle for a plasma etching device has a wall component, and the wall component has the anodized titanium material of the first scheme of the present invention, which defines an internal space, and the wall component has at least a bottom surface, and the wall component has: a gas inlet port, so that the processing gas of plasma etching flows into the internal space; and a plurality of gas exhaust holes, which are arranged on the bottom surface, so that the processing gas flows out from the internal space, and the anodized titanium layer is exposed at least on the inner peripheral surface of the plurality of gas exhaust holes.
[0028] The fifth scheme of the present invention is a method for manufacturing anodized titanium material, characterized in that it is a method for manufacturing anodized titanium material, and the method for manufacturing anodized titanium material includes: step (a), preparing a to-be-treated material having titanium on its surface; and step (b), anodizing the to-be-treated material, wherein step (b) includes step (b1), anodizing the to-be-treated material in a first electrolyte, wherein in step (b1), the first electrolyte includes a non-aqueous solvent and a fluoride ion source that can be uniformly mixed with water, and further includes water or does not contain water, the temperature of the first electrolyte is below 10°C, the electrolysis voltage is below 200V, and the relative flow rate of the first electrolyte relative to the to-be-treated material is above 1 cm / second and below 5 cm / second.
[0029] In the present invention, the relative flow velocity refers to the relative velocity of the electrolyte relative to the material to be treated immediately before it reaches the material to be treated. By using an electromagnetic flow meter (e.g., three-dimensional electromagnetic flow meter ACM3-RS (manufactured by JFE Advantech), three-dimensional electromagnetic flow meters VM-1001 and VMT3-200-13P (manufactured by KENEK Corporation), electromagnetic micro flow meters VM-801L and VMT2-50-08PS (manufactured by KENEK Corporation), and electromagnetic flow meters VP2500 and VPT2-200-08CA (manufactured by KENEK Corporation), laser Doppler flow meters (e.g., PowerSight (manufactured by TSI Corporation), FiberFlow, FlowLite, and FlowExplorer (all manufactured by Dantec Dynamics Corporation), and 2D-FLVSystem 8835 and Smart The measuring head or probe of a known flow meter such as LDVIII (both manufactured by Kano Max Co., Ltd., Japan) is arranged at a corresponding position to measure the flow rate of the electrolyte at a position just before (for example, 2 cm before) the treated material (the surface to be anodized), and the relative flow rate can be measured.
[0030] In the fifth embodiment of the present invention, it is preferred that the step (b) further includes a step (b2), wherein the material to be treated after the step (b1) is anodized in a second electrolyte having a fluoride ion source concentration of less than 10 ppm by mass calculated as fluorine atoms or containing no fluoride ion source, and in the step (b2), the temperature of the second electrolyte is less than 70°C, the electrolysis voltage is less than 200V, and the relative flow rate of the second electrolyte to the material to be treated is greater than 1 cm / second and less than 5 cm / second.
[0031] Effects of the Invention
[0032] As for the anodized titanium material of the first embodiment of the present invention, the anodized titanium layer has improved voltage resistance, and thus can be suitably used for applications where a high voltage is applied between the titanium base material and the anodized titanium layer (e.g., applications exposed to a plasma atmosphere, electrostatic chucks, etc.). Furthermore, the anodized titanium material of the first embodiment of the present invention has sufficient hardness and surface smoothness, and thus can also be preferably used as a component of a vacuum device requiring vacuum sealing properties.
[0033] The electrostatic chuck for a plasma etching device according to the second aspect of the present invention has the anodized titanium layer of the anodized titanium material according to the first aspect of the present invention on the outermost surface, so that insulation breakdown can be suppressed even under the conditions of plasma etching. In addition, since the difference in thermal expansion coefficients between titanium and anodized titanium is small and has high heat resistance, the generation of cracks can be suppressed even under the conditions of plasma etching.
[0034] The cooling plate for a plasma etching device according to the third aspect of the present invention has the anodized titanium layer of the anodized titanium material according to the first aspect of the present invention on the outermost surface, so even if a high-frequency voltage is applied to the cooling plate in a plasma etching device, insulation breakdown can be suppressed. In addition, since the difference in thermal expansion coefficients between titanium and anodized titanium is small and has high heat resistance, the generation of cracks can be suppressed even under the conditions of plasma etching.
[0035] In a nozzle for a plasma etching device, it is difficult to provide a strong protective film such as a ceramic sprayed film on the inner peripheral surface of the gas exhaust hole. In the nozzle for a plasma etching device of the fourth scheme of the present invention, the wall member has the anodized titanium material of the first scheme of the present invention, and the anodized titanium layer is exposed on the inner peripheral surface of at least a plurality of gas exhaust holes. That is, in the nozzle for a plasma etching device of the present invention, the anodized titanium layer acts as a protective film at least on the inner peripheral surface of the gas exhaust hole. As described above, the anodized titanium material of the present invention has high heat resistance due to the small difference in thermal expansion coefficient between the titanium base material and the anodized titanium layer, and therefore the generation of cracks in the anodized titanium layer is suppressed even under the conditions of plasma etching treatment. Therefore, according to the nozzle for a plasma etching device of the present invention, the inner peripheral surface of the gas exhaust hole can be properly protected even under the conditions of plasma etching treatment.
[0036] According to the method for producing an anodized titanium material according to the fifth aspect of the present invention, an anodized titanium material having improved withstand voltage can be produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a flowchart for explaining a method S100 for producing an anodized titanium material according to an embodiment of the present invention.
[0038] Figure 2 This is a flowchart for explaining a method S200 for manufacturing an anodized titanium material according to another embodiment of the present invention.
[0039] Figure 3 This is a flowchart for explaining a method S300 for manufacturing an anodized titanium material according to still another embodiment of the present invention.
[0040] Figure 4 It is a cross-sectional view schematically illustrating an anodized titanium material 100 according to one embodiment of the present invention.
[0041] Figure 5 This is a cross-sectional view schematically illustrating an anodized titanium material 200 according to another embodiment of the present invention.
[0042] Figure 6 This is a cross-sectional view schematically illustrating an anodized titanium material 300 according to still another embodiment of the present invention.
[0043] Figure 7 1 is a cross-sectional view schematically illustrating an electrostatic chuck 100 ′ together with a plasma etching apparatus 1000 according to an embodiment of the present invention.
[0044] Figure 8 (A) is a cross-sectional SEM image of the anodized titanium material obtained in Example 1. Figure 8(B) is a surface SEM image of the anodized titanium layer.
[0045] Fig. 9 This is a high-magnification cross-sectional SEM image of the anodized titanium material obtained in Example 1. Fig. 9 (A) is a cross-sectional SEM image of the surface layer of the anodized titanium layer. Fig. 9 (B) is a cross-sectional SEM image of the central portion of the anodized titanium layer. Fig. 9 (C) is a cross-sectional SEM image of the interface between the anodized titanium layer and the titanium base material.
[0046] Fig.10 This is a SEM image of a cross section perpendicular to the thickness direction of the anodized titanium layer obtained in Example 1. Fig.10 (A) is the observation result of a location relatively shallow from the surface. Fig.10 (B) is the observation result of a location deeper from the surface.
[0047] Fig.11 This is a cross-sectional SEM image of the anodized titanium material obtained in Comparative Example 1.
[0048] Fig.12 (A) is a cross-sectional SEM image of the anodized titanium material obtained in Comparative Example 4. Fig.12 (B) is a surface SEM image of the anodized titanium material obtained in Comparative Example 4.
[0049] Fig.13 Graph showing the temperature dependence of the withstand voltage of the anodized titanium oxide layers obtained in Examples 1 and 2. Fig.13 (A) is a graph showing the temperature dependence of the withstand voltage of the anodized titanium layer obtained in Example 1. Fig.13 (B) is a graph showing the temperature dependence of the withstand voltage of the anodized titanium layer obtained in Example 2.
[0050] Fig.14 Graphs showing the temperature dependence of the withstand voltage per unit film thickness of the anodized titanium oxide layers obtained in Examples 1 and 2 and the anodized aluminum films obtained in Comparative Examples 5 and 6.
[0051] Fig.15 This is a cross-sectional SEM image of the anodized titanium material obtained in Example 3. Fig.15 (A) is a cross-sectional SEM image capturing the entire anodized titanium layer. Fig.15 (B) is a cross-sectional SEM image of the vicinity of the interface between the anodized titanium layer and the titanium base material.
[0052] Fig.16 This is a surface SEM image of the anodized titanium material obtained in Example 3.
[0053] Fig.17 This is a cross-sectional SEM image of the anodized titanium material obtained in Example 3 and a diagram showing an electron beam irradiated portion in EDS measurement.
[0054] Fig.18 These are SEM images of a cross section of the anodized titanium layer obtained in Example 3 and SEM images of the surface layer side and the base material side of the separated anodized titanium layer, and are diagrams showing changes in the morphology of the porous structure accompanying changes in temperature. Fig.18 The left column (A) (D) (G) is the initial SEM image at room temperature (26°C). Fig.18 The middle columns (B), (E), and (H) are SEM images at 150°C. Fig.18 The right columns (C), (F), and (I) are SEM images when the sample temperature is restored to room temperature (26°C). Fig.18 The upper row (A), (B), and (C) are SEM images of the surface of the anodized titanium layer on the surface side. Fig.18 The middle row (D), (E), and (F) are SEM images of the surface of the anodized titanium layer on the base material side. Fig.18 The lower row (G)(H)(I) is a cross-sectional SEM image of the anodized titanium layer. DETAILED DESCRIPTION
[0055] The above-mentioned effects and benefits of the present invention are clarified by the specific embodiments described below. Below, the embodiments of the present invention are described with reference to the accompanying drawings. However, the present invention is not limited to these modes. It should be noted that the drawings do not necessarily reflect the correct dimensions. In addition, in the drawings, some of the figure marks are sometimes omitted. In this specification, unless otherwise specified, for numerical values A and B, the expression "A to B" means "above A and below B". In the case where only numerical value B is given a unit in the expression, the unit also applies to numerical value A. In addition, unless otherwise specified, the statements of "or" and "or" refer to logical disjunction.
[0056] <Method for producing anodized titanium material>
[0057] Figure 1 This is a flowchart for explaining a method S100 for manufacturing an anodized titanium material according to an embodiment of the present invention (hereinafter sometimes referred to as “manufacturing method S100 ”). Manufacturing method S100 includes a preparation step S10 and an anodizing step S20 . Anodizing step S20 includes a first anodizing step S21 .
[0058] Preparation step S10 is a step of preparing a treated material having titanium on the surface. As the treated material, for example, a titanium component can be used directly. In addition, for example, the treated material can also be obtained by forming a titanium layer on the surface of a metal base material other than titanium (such as aluminum, stainless steel or a combination thereof). There is no particular restriction on the method of forming a titanium layer on the surface of a metal base material other than titanium. For example, known methods such as sputtering, ionized evaporation, and vacuum evaporation can be used. In the case of forming a titanium layer on the surface of a metal base material other than titanium, the thickness of the titanium layer is usually more than 5 μm, preferably more than 10 μm, and more preferably more than 20 μm. In the case of forming a titanium layer on the surface of a metal base material other than titanium, the thickness of the titanium layer is more than the above-mentioned lower limit, so that it is easy to grow an anodized titanium layer with sufficient film thickness, thereby improving the voltage resistance of the anodized titanium layer. There is no particular restriction on the upper limit of the thickness of the above-mentioned titanium layer, for example, it can be set to less than 100 μm.
[0059] The arithmetic mean roughness Ra of the titanium surface of the material to be treated prepared in the preparation step S10 is preferably less than 1 μm, more preferably less than 0.5 μm, and the lower limit thereof is not particularly limited, and may be, for example, 0.1 μm or more.
[0060] The maximum height roughness Rz of the titanium surface of the workpiece prepared in the preparation step S10 is preferably less than 10 μm, more preferably less than 5 μm, and the lower limit thereof is not particularly limited, and may be, for example, 1 μm or more.
[0061] By making the arithmetic mean roughness Ra and the maximum height roughness Rz of the titanium surface of the treated material prepared in the preparation step S10 smaller than the above upper limit, it becomes easy to manufacture an anodized titanium material having a high smoothness of the anodized titanium layer described later. It should be noted that in this specification, the arithmetic mean roughness Ra and the maximum height roughness Rz of the surface refer to the arithmetic mean roughness and the maximum height roughness specified in JIS B0601, respectively.
[0062] The preparation step S10 may include a step of grinding the titanium surface of the material to be processed. The method of grinding the titanium surface of the material to be processed is not particularly limited, and known methods such as grinding paper, polishing, chemical polishing, and chemical mechanical polishing (CMP) may be used.
[0063] The preparation step S10 may also include a step of pre-treating the material to be treated. Examples of pre-treatment include degreasing, pickling, washing, etching, and combinations thereof. The degreasing treatment may be performed by a known method, for example, preferably by alkaline electrolytic degreasing using the material to be treated as an anode. By performing alkaline electrolytic degreasing using the material to be treated as an anode, it becomes easy to improve the adhesion of the anodized titanium oxide layer. After alkaline electrolytic degreasing using the material to be treated as an anode, the material to be treated is preferably pickled in order to remove the oxide film.
[0064] The anodizing step S20 is a step of anodizing the material to be treated prepared in the preparation step S10. The anodizing step S20 includes a first anodizing step S21. The first anodizing step S21 is a step of anodizing the material to be treated prepared in the preparation step S10 in a first electrolyte. Through the first anodizing step S21, a porous first anodized titanium layer grows on the surface of the titanium matrix of the material to be treated.
[0065] The electrolytic cell used in the first anodizing step S21 is not particularly limited, and a known electrolytic cell that can be used for anodizing can be used. As such an electrolytic cell, for example, an electrolytic cell including: a container for storing an electrolyte, a stirring device for stirring the electrolyte in the container, and a cooling device for cooling the electrolyte in the container can be cited. In addition, the cathode used in the first anodizing step S21 is not particularly limited, and a known cathode that is insoluble in the first electrolyte can be used.
[0066] In the first anodizing step S21, the first electrolyte solution includes a non-aqueous solvent that can be uniformly mixed with water and a fluoride ion source. The first electrolyte solution may further contain water or may not contain water.
[0067] As the above-mentioned non-aqueous solvent, for example, ethylene glycol, glycerol, ethanol, isopropanol and their combination and other organic solvents that can be uniformly mixed with water can be preferably used, wherein ethylene glycol, glycerol or their combination can be particularly preferably used. The content of the non-aqueous solvent in the first electrolyte is preferably 88 to 97% by mass, more preferably 90 to 96% by mass based on the total amount of the electrolyte.
[0068] The fluoride ion source is a substance that provides fluoride ions in the electrolyte, acts as an electrolyte in the first electrolyte, and acts as a solubilizing agent that dissolves the titanium oxide in the electrolyte. The fluoride ion source is preferably soluble in the non-aqueous solvent when the first electrolyte does not contain water, and is preferably soluble in a mixture of the non-aqueous solvent and water when the first electrolyte contains water. Examples of the fluoride ion source include: hydrogen fluoride; metal fluorides such as lithium fluoride, sodium fluoride, potassium fluoride, potassium hydrogen fluoride, cesium fluoride, magnesium fluoride, and zinc fluoride; ammonium fluoride, ammonium hydrogen fluoride (acidic ammonium fluoride); amine salts such as trimethylamine trihydrofluoride, triethylamine trihydrofluoride, tributylamine trihydrofluoride, and hydrogen fluoride pyridine, or organic base-hydrogen fluoride adducts; etc. The fluoride ion source can be used alone or in combination of two or more. Among them, from the viewpoint of improving the voltage resistance of the anodized titanium layer, it is particularly preferred to use ammonium fluoride (NH4F), or ammonium bifluoride (NH4F·HF), or a combination thereof. The content of the fluoride ion source in the first electrolyte (when two or more fluoride ion sources are used in combination, it is the total content.) It is preferably 2000 to 5000 mass ppm, more preferably 3000 to 4000 mass ppm, and particularly preferably 3250 to 3750 mass ppm based on the total amount of the electrolyte, calculated by fluorine atoms. By having the concentration of the fluoride ion source in the first electrolyte within the above range, it becomes easy to form a thicker anodized titanium layer, and therefore it becomes easy to form an anodized titanium layer with improved voltage resistance. The content of the fluoride ion source as a whole can be, for example, 2 to 5 mass % based on the total amount of the electrolyte.
[0069] In the first electrolyte, water acts as an ion to titanium oxide (O 2- ) source. When the non-aqueous solvent does not have the ability to supply oxide ions to titanium under electrolysis conditions, the first electrolyte preferably contains water. When the non-aqueous solvent has the ability to supply oxide ions to titanium, the first electrolyte may not contain water. For example, when the non-aqueous solvent is ethylene glycol, the first electrolyte preferably contains water. When the non-aqueous solvent is glycerol, the first electrolyte may not contain water. As water, deionized water can be preferably used. When the first electrolyte contains water, from the viewpoint of forming a thicker anodized titanium layer and improving the voltage resistance, its content is preferably 1 to 10% by mass based on the total amount of the electrolyte, more preferably 2 to 9% by mass, and particularly preferably 4 to 6% by mass.
[0070] In a preferred embodiment, the first electrolyte comprises, based on the total amount of the electrolyte, 88 to 97 mass %, more preferably 90 to 96 mass %, and particularly preferably 90 to 93 mass % of ethylene glycol; 1 to 10 mass %, more preferably 2 to 9 mass %, and particularly preferably 4 to 6 mass % of water; and a fluoride ion source in an amount of 2000 to 5000 mass ppm, more preferably 3000 to 4000 mass ppm, and particularly preferably 3250 to 3750 mass ppm, calculated as fluorine atoms.
[0071] In the first anodizing step S21, the temperature of the first electrolyte is maintained at 10°C or less, preferably 5°C or less. By keeping the temperature of the first electrolyte below the above upper limit, a thicker anodized titanium layer can be formed to improve the withstand voltage. In addition, from the viewpoint of improving the adhesion and withstand voltage of the anodized titanium layer, the temperature of the first electrolyte is preferably above 0°C, more preferably above 3°C. When controlling the temperature of the first electrolyte, there is no particular limitation, and a known cooling device for an electrolytic cell can be used.
[0072] In the first anodizing step S21, the electrolysis voltage is 200V or less, preferably 150V or less, more preferably 140V or less, and particularly preferably 135V or less. By the electrolysis voltage being below the above upper limit, the following situation can be suppressed: discontinuous electrochemical oxidation with spark discharge, i.e., microarc oxidation, occurs and coarse voids are generated in the anodized titanium layer, which damages the uniformity and surface smoothness of the anodized titanium layer and reduces the voltage resistance. The lower limit of the electrolysis voltage is usually 10V or more, preferably 40V or more.
[0073] In the first anodizing step S21, the relative flow rate of the first electrolyte to the workpiece is maintained at 1 cm / sec or more and 5 cm / sec or less. The relative flow rate refers to the relative speed of the electrolyte to the workpiece immediately before reaching the workpiece. By combining electromagnetic flowmeters (such as three-dimensional electromagnetic flowmeter ACM3-RS (manufactured by JFE Advantech), three-dimensional electromagnetic flowmeters VM-1001 and VMT3-200-13P (manufactured by KENEK Corporation), electromagnetic micro-flowmeters VM-801L and VMT2-50-08PS (manufactured by KENEK Corporation), and electromagnetic flowmeters VP2500 and VPT2-200-08CA (manufactured by KENEK Corporation), laser Doppler flowmeters (such as PowerSight (manufactured by TSI Corporation), FiberFlow, FlowLite and FlowExplorer (all manufactured by Dantec Dynamics Corporation) and 2D-FLVSystem 8835 and Smart LDVIII (all manufactured by Kano Max Co., Ltd., Japan). The measuring head or probe of a known flowmeter such as ) is arranged at a corresponding position to measure the flow rate of the electrolyte at a position just before the treated material (the surface to be anodized) (for example, 2 cm in front), and the relative flow rate can be measured. By making the relative flow rate of the first electrolyte above the above lower limit, the excessive rise in substrate temperature can be suppressed. In addition, the reagent can be efficiently supplied to the surface of the component, thereby forming a thicker anodized titanium layer and improving the voltage resistance. In addition, by making the relative flow rate of the first electrolyte below the above upper limit, the uniformity of the film thickness of the anodized titanium layer can be improved.
[0074] In the first anodizing step S21, the electrolytic current density is a value obtained by dividing the electrolytic current by the area of the titanium surface of the treated material, and is preferably 1 mA / cm 2 More preferably, 5 mA / cm 2 More than, preferably 100 mA / cm 2 Below, more preferably 50mA / cm 2 By making the electrolytic current density be above the above lower limit, it is easy to increase the generation rate of titanium oxide and form a thicker first anodic titanium oxide layer and improve the withstand voltage. In addition, by making the electrolytic current density be below the above upper limit, it is easy to suppress micro-arc oxidation.
[0075] In the anodizing step S20, the electrolysis time also depends on the composition and temperature of the electrolyte, as well as other conditions such as the flow rate and the electrolysis voltage, and therefore cannot be generally specified, but is preferably set to a time when the film thickness of the anodized titanium layer becomes 20 μm or more and less than 80 μm. If the electrolysis time is too short, the anodized titanium layer cannot grow to a sufficient film thickness, and if the electrolysis time is too long, there is a tendency for the residue on the outermost surface of the anodized titanium layer to increase. The appropriate electrolysis time can be easily determined by preliminary experiments.
[0076] After the anodizing step S20 is completed, a cleaning process may be further performed to remove the electrolyte from the surface of the treated material. During the cleaning process, a known polar solvent such as water, ethanol, acetone, isopropyl alcohol, etc. may be used.
[0077] Figure 2 This is a flowchart for explaining a method S200 for manufacturing anodized titanium material according to another embodiment (hereinafter sometimes referred to as "manufacturing method S200"). Manufacturing method S200 is different from manufacturing method S100 in that it includes an anodizing step S20' having a first anodizing step S21 and a second anodizing step S22 instead of anodizing step S20. The preparation step S10 and the first anodizing step S21 are as described above in relation to manufacturing method S100.
[0078] The second anodizing step S22 is a step in which the material to be treated that has passed through the first anodizing step S21 is anodized in a second electrolyte solution in which the concentration of a fluoride ion source is less than 10 mass ppm in terms of fluorine atoms or does not contain a fluoride ion source. By passing through the second anodizing step S22, a second anodized titanium layer grows between the titanium matrix of the material to be treated and the first anodized titanium layer grown in the first anodizing step S21. The fluorine content (unit: atomic %) of the second anodized titanium layer is lower than the fluorine content (unit: atomic %) of the first anodized titanium layer. In addition, according to the manufacturing method S200 having the second anodizing step S22, the adhesion of the anodized titanium layer can be improved, and in addition, the voltage resistance of the anodized titanium layer can be further improved.
[0079] The electrolytic cell used in the second anodizing step S22 is not particularly limited, and the same electrolytic cell as the electrolytic cell described above with respect to the first anodizing step S21 can be used. In addition, the cathode used in the second anodizing step S22 is not particularly limited, and a known cathode that is insoluble in the second electrolyte can be used.
[0080] In the second anodizing step S22, the concentration of the fluoride ion source in the second electrolyte is 10 mass ppm or less, preferably less than 5 mass ppm, particularly preferably less than 3 mass ppm, and may be 0 mass ppm in terms of fluorine atoms based on the total amount of the electrolyte.
[0081] As for the second electrolyte, as a solvent, it may contain a non-aqueous solvent or may not contain a non-aqueous solvent, and may contain water or may not contain water. Among them, the second electrolyte preferably contains a substance having the ability to supply oxide ions to titanium. In the second electrolyte, the solvent may have the ability to supply oxide ions, the solute may have the ability to supply oxide ions, or both the solvent and the solute may have the ability to supply oxide ions.
[0082] As the solvent of the second electrolyte, there is no particular limitation, and a non-aqueous solvent, water or a mixture thereof can be used. As the non-aqueous solvent in the second electrolyte, for example, ethylene glycol, glycerol, ethanol, isopropanol and a combination thereof can be preferably used as an organic solvent that can be uniformly mixed with water, wherein ethylene glycol, glycerol or a combination thereof can be particularly preferably used. In addition, water acts as an oxide ion source for titanium, so it can be preferably used. In addition, as water, deionized water or pure water can be preferably used. In one embodiment, a mixed solvent containing a non-aqueous solvent exceeding 0 mass % and less than 95 mass %, and water exceeding 5 mass % and less than 100 mass % based on the total solvent amount can be preferably used as the solvent of the second electrolyte. In another embodiment, a solvent composed of water can be preferably used as the solvent of the second electrolyte.
[0083] There is no particular limitation on the solute of the second electrolyte. For example, electrolytes such as hydrogen peroxide, hydrogen chloride, formic acid, oxalic acid, phosphoric acid, and phosphates (e.g., potassium phosphate, etc.) can be used, among which hydrogen peroxide, formic acid, or a combination thereof can be preferably used. Two or more solutes can also be used in combination. Among them, in the case where the solvent does not have the ability to supply oxide ions to titanium, the second electrolyte preferably includes: a solute or ion having the ability to supply oxide ions; or a solute or ion of a chemical species having the ability to supply oxide ions by being reduced at the cathode (e.g., hydroxide ions, peroxide ions, carboxylic acid ions, phosphate ions, etc.).
[0084] It should be noted that hydrogen peroxide is reduced at the cathode to provide hydroxide ions (OH - The hydroxide ions make the acidity of the second electrolyte tend to be alkaline and improve the conductivity, and also act as oxide ions (O 2-Thus, hydrogen peroxide can suppress the increase of chemical species other than hydrogen ions that do not contribute to the necessary reaction, and ensure conductivity and oxide ion supply source, so hydrogen peroxide can be particularly preferably used as the solute of the second electrolyte.
[0085] In a preferred embodiment, the second electrolyte contains, based on the total amount of the electrolyte, 89.9-99.6 mass % of ethylene glycol, 0.1-3 mass % of hydrogen peroxide, and 0.3-10 mass % of water.
[0086] In the second anodizing step S22, the temperature of the second electrolyte is maintained at 70°C or less, preferably 50°C or less. By keeping the temperature of the second electrolyte below the above upper limit, a thicker anodized titanium layer can be formed to improve the voltage resistance. In addition, from the viewpoint of reaction speed, the temperature of the second electrolyte is usually above 0°C, preferably above 5°C. When controlling the temperature of the second electrolyte, there is no particular limitation, and a known heating device or cooling device for an electrolytic cell can be used.
[0087] In the second anodizing step S22, the electrolysis voltage is below 200V, preferably below 155V, more preferably below 140V, and particularly preferably below 130V. Micro-arc oxidation may or may not occur in the second anodizing step S22, but if micro-arc oxidation occurs in step S22, coarse voids with a pore size of more than 1 μm are generated in the second anodized titanium layer. By having the electrolysis voltage below the above upper limit, excessive micro-arc oxidation can be suppressed, thereby reducing the adhesion of the titanium base material to the anodized titanium layer. The lower limit of the electrolysis voltage is usually above 40V, preferably above 70V.
[0088] In the second anodizing step S22, the relative flow rate of the second electrolyte relative to the treated material is maintained at 1 cm / second or more and 5 cm / second or less. The above relative flow rate refers to the relative speed of the electrolyte relative to the treated material just before reaching the treated material, and the determination method is as described above for the first anodizing step S21. By making the relative flow rate of the second electrolyte above the above lower limit, the excessive rise in substrate temperature can be suppressed. In addition, the reagent can be efficiently supplied to the surface of the component, thereby forming a thicker anodized titanium layer and improving the voltage resistance. In addition, by making the relative flow rate of the second electrolyte below the above upper limit, the uniformity of the film thickness of the anodized titanium layer can be improved.
[0089] In the second anodizing step S22, the electrolytic current density is the value obtained by dividing the electrolytic current by the area of the titanium surface of the treated material, and is preferably 1 mA / cm 2 More preferably, 5 mA / cm 2 More than, preferably 100 mA / cm2 Below, more preferably 50mA / cm 2 Below. By the electrolytic current density being above the above lower limit, it is easy to improve the generation rate of titanium oxide and form a thicker second anodized titanium layer and improve the withstand voltage. In addition, by the electrolytic current density being below the above upper limit, a dense and smooth anodized film can be made.
[0090] In the anodizing step S20', the electrolysis time in the first anodizing step S21 and the second anodizing step S22 also depends on the composition and temperature of the electrolyte, as well as other conditions such as flow rate and electrolysis voltage, so it cannot be stipulated in general, but it is preferably set to the time when the total film thickness of the anodized titanium layer (that is, the total film thickness of the first anodized titanium layer grown in the first anodizing step S21 and the second anodized titanium layer grown in the second anodizing step S22) becomes greater than 20μm and less than 80μm. In addition, the electrolysis time in the second anodizing step S22 can be set, for example, to the time when the film thickness of the second anodized titanium layer is preferably 0.1 to 5μm, more preferably 0.5 to 3μm, and further preferably 1 to 3μm. If the electrolysis time is too short, the anodized titanium layer cannot grow to a sufficient film thickness, and even if the electrolysis time is too long, the increase in film thickness is not commensurate with the electrolysis time. The appropriate electrolysis time can be easily determined by preliminary experiments.
[0091] After the first anodizing step S21, the material to be treated may be directly supplied to the second anodizing step S22 without cleaning, or after the first anodizing step S21 and before the second anodizing step S22, a cleaning treatment may be performed to remove the first electrolyte from the surface of the material to be treated. However, from the viewpoint of improving the adhesion of the anodized titanium layer, it is preferred not to perform a cleaning treatment after the first anodizing step S21 and before the second anodizing step S22, or even if it is performed, it is kept to a minimum, and the cleaning time may be preferably set to less than 60 seconds, more preferably less than 10 seconds. In addition, as a cleaning liquid, for example, a known neutral solvent such as water, ethanol, ethylene glycol, acetone, isopropanol, etc. may be preferably used as a cleaning liquid, wherein, from the viewpoint of improving the adhesion of the anodized titanium layer, a neutral organic solvent such as ethanol, ethylene glycol, acetone, etc. may be preferably used as a cleaning liquid.
[0092] After the anodizing step S20' is completed, a cleaning process may be further performed to remove the electrolyte from the surface of the treated material. During the cleaning process, a known solvent such as water, ethanol, ethylene glycol, acetone, isopropyl alcohol, etc. may be used as the cleaning liquid.
[0093] In the above description of the present invention, although the examples of the manufacturing method S100 and S200 of anodized titanium material having the preparation step S10 and the anodizing step S20 or S20' are listed, the present invention is not limited to this method. For example, the manufacturing method of anodized titanium material can also be adopted in the following manner: after the anodizing step, there is also a step of grinding the surface of the anodized layer. Figure 3 This is a flowchart for explaining a method S300 for manufacturing anodized titanium material according to another embodiment of the present invention (hereinafter sometimes referred to as “manufacturing method S300”). Figure 3 Sometimes Figures 1-2 The element annotations shown in Figures 1-2 The same reference numerals as those in the figure are used, and their description is omitted. The manufacturing method S300 includes a polishing step S30 in addition to the preparation step S10 and the anodizing step S20 described above.
[0094] The grinding process S30 is a process in which the surface of the anodized titanium layer formed in the anodizing process S20 is ground after the anodizing process S20. By passing through the grinding process S30, the residue on the surface of the anodized titanium layer can be removed, and the smoothness of the surface can be further improved. There is no particular limitation on the grinding method in the grinding process S30, and known grinding methods such as grinding and polishing using grinding paper can be used. In the grinding process S30, it is preferred to grind in a manner such that the arithmetic mean roughness Ra of the surface of the anodized titanium layer becomes less than 1.6 μm, more preferably less than 0.8 μm, and the maximum height roughness Rz of the surface becomes less than 6.3 μm, more preferably less than 3.2 μm. It should be noted that in this specification, the arithmetic mean roughness Ra and the maximum height roughness Rz refer to the arithmetic mean roughness Ra and the maximum height roughness Rz specified in JIS B0601.
[0095] After the polishing step S30 , a cleaning process may be further performed to remove polishing debris, etc. When performing the cleaning process, for example, a known solvent such as water, ethanol, or acetone may be used as a cleaning liquid.
[0096] <Anodized titanium material>
[0097] Figure 4It is a cross-sectional view schematically illustrating an anodized titanium material 100 according to an embodiment of the present invention. The anodized titanium material 100 comprises a titanium base material 10 and an anodized titanium layer 20 provided on the surface of the titanium base material 10, the anodized titanium layer 20 comprises a porous first anodized titanium layer 21, the anodized titanium layer 20 has a withstand voltage of 500V or more at 25°C, a Vickers hardness of 200 or more, a film thickness of 20μm or more and less than 80μm, an arithmetic mean roughness Ra of the surface of less than 1.6μm, a maximum height roughness Rz of the surface of less than 6.3μm, and no pore cross-section having a shape that can contain a circle with a diameter of 0.5μm or more is observed in any of the cross-section and the surface perpendicular to the thickness direction of the anodized titanium layer 20. Such an anodized titanium material 100 can be manufactured by the anodized titanium material manufacturing method S100 (described above). Figure 1 ) to get it.
[0098] The withstand voltage of the anodized titanium layer 20 at 25°C is 500V or more, preferably 1000V or more. There is no particular restriction on the upper limit of the withstand voltage at 25°C, but it is usually 5000V or less, and preferably 3000V or less from the viewpoint of ease of manufacturing. The anodized titanium material 100 has an anodized titanium layer 20 with improved withstand voltage, and therefore can be preferably used for applications where high voltage is applied, such as exposure to a plasma atmosphere. It should be noted that in this specification, the withstand voltage of the anodized titanium layer refers to the withstand voltage measured as the last applied voltage at which no insulation breakdown occurs in the anodized titanium layer, while a DC voltage is boosted and applied between the base material and the surface of the anodized titanium layer until insulation breakdown occurs in the anodized titanium layer.
[0099] The Vickers hardness of the anodized titanium layer 20 is 200 or more, preferably 250 or more. In this specification, the Vickers hardness of the anodized titanium layer refers to the Vickers hardness measured from the surface of the anodized titanium layer by a micro Vickers hardness test in accordance with JIS Z2244.
[0100] The film thickness of the anodized titanium layer 20 is 20 μm or more and less than 80 μm, preferably 25 μm or more, more preferably 40 μm or more, and preferably less than 60 μm. By having a film thickness of more than the above lower limit, the withstand voltage can be improved. In addition, it is difficult to obtain an anodized titanium layer 20 with a film thickness of more than 80 μm. It should be noted that the film thickness of the anodized titanium layer can be measured by an eddy current film thickness meter (e.g., MP2 / O type manufactured by Helmut Fischer, etc.).
[0101] The arithmetic mean roughness Ra of the surface of the anodized titanium layer 20 is less than 1.6 μm, preferably less than 0.8 μm. The lower limit thereof is not particularly limited, and may be, for example, 0.1 μm or more.
[0102] The maximum height roughness Rz of the surface of the anodized titanium layer 20 is less than 6.3 μm, preferably less than 3.2 μm. The lower limit thereof is not particularly limited, and may be, for example, 1 μm or more.
[0103] The anodized titanium material 100 having the anodized titanium layer 20 having a surface arithmetic mean roughness Ra and a surface maximum height roughness Rz less than the above upper limit has high surface smoothness, and thus can be preferably used for a component requiring vacuum sealing in a vacuum device, for example. It should be noted that in this specification, the surface arithmetic mean roughness Ra and the maximum height roughness Rz refer to the arithmetic mean roughness and the maximum height roughness specified in JIS B0601, respectively.
[0104] In any of the cross-sections and surfaces perpendicular to the thickness direction of the first anodized titanium layer 21, no pore cross-sections having a shape that can contain a circle with a diameter of 0.5 μm or more are observed. Preferably, in any of the cross-sections and surfaces perpendicular to the thickness direction of the first anodized titanium layer 21, no pore cross-sections having a shape that can contain a circle with a diameter of 0.4 μm or more are observed. It should be noted that in any of the cross-sections and surfaces perpendicular to the thickness direction of the anodized titanium layer, no pore cross-sections having a shape that can contain a circle with a diameter greater than the above-mentioned specified value are observed. This can be determined as follows: in any of the scanning electron microscope images (SEM images) of the surface of the anodized titanium material, the anodized titanium layer, and the SEM images of the surface after the anodized titanium layer is polished, no pore cross-sections (openings) having a shape that can contain a circle with a diameter greater than the above-mentioned specified value are observed. The conditions for SEM observation can be, for example, acceleration voltage: 5.0 to 10.0 kV, detection mode: reflected electron detection, and magnification: 10,000 times. According to the first anodized titanium layer 21 having a pore cross section as described above and having no coarse voids, the uniformity of the film is high, so that the withstand voltage can be improved. The first anodized titanium layer 21 has a plurality of tubular pores extending in a direction intersecting the surface of the anodized titanium layer 20. That is, the first anodized titanium layer 21 has many pores grown in a tubular or conical shape in the thickness direction, and generally the size (diameter) of each tubular pore is larger as it approaches the surface layer, and smaller as it approaches the titanium base material 10. The cross section perpendicular to the long dimension direction (extension direction) of each tubular pore has a shape close to a circle, and its diameter (the diameter in the long axis direction when it is not a perfect circle) is generally less than 0.3 μm, and typically less than 0.2 μm. In contrast, for example, in the case where micro-arc oxidation occurs during the growth process of the anodized titanium layer, coarse voids will remain in the part where micro-arc oxidation occurs regardless of the position in the thickness direction. The effect of micro-arc oxidation on forming voids is roughly isotropic in the plane direction (i.e., the direction perpendicular to the thickness direction of the anodized titanium layer.), so a pore section or opening with a relatively high roundness appears on the section or surface perpendicular to the thickness direction of the anodized titanium layer. Therefore, the voids generated by micro-arc oxidation have a pore section (or opening) on the section or surface perpendicular to the thickness direction of the anodized titanium layer, and the pore section (or opening) has a circular shape that can contain a diameter greater than the above lower limit.
[0105] The anodized titanium layer 20 has the following unique properties: the withstand voltage becomes the lowest near room temperature (25°C), the withstand voltage increases at a temperature higher than room temperature (25°C), and the withstand voltage increases at a temperature lower than room temperature (25°C). That is, the anodized titanium layer 20 has a property opposite to that of the conventionally known anodic aluminum film, that is, the withstand voltage at 150°C is higher than the withstand voltage at 25°C. Although not limited by theory, it is believed that the property of the withstand voltage increasing at high temperatures is caused by the fact that many pores that grow in a tubular or conical shape in the thickness direction of the anodized titanium layer 20 shrink when the temperature rises from room temperature.
[0106] Figure 5 FIG. 2 is a cross-sectional view schematically illustrating an anodized titanium material 200 according to another embodiment of the present invention. Figure 5 In, yes Figure 4 The element annotations shown in Figure 4 The same reference numerals as those in the figure are omitted for explanation. The anodized titanium material 200 is different from the anodized titanium material 100 in that it has an anodized titanium layer 20' instead of the anodized titanium layer 20 composed of the first anodized titanium layer 21. The anodized titanium layer 20' has a second anodized titanium layer 22 provided between the titanium base material 10 and the first anodized titanium layer 21 in addition to the first anodized titanium layer 21. Such an anodized titanium material 200 can be obtained by the anodized titanium material manufacturing method S200 described above.
[0107] The first anodized titanium layer 21 is as described above with respect to the anodized titanium material 100. The withstand voltage, Vickers hardness, film thickness, and arithmetic mean roughness Ra and maximum height roughness Rz of the anodized titanium layer 20' are the same as those of the anodized titanium layer 20 described above.
[0108] The film thickness of the second anodized titanium layer 22 is preferably 0.1 to 5 μm, more preferably 0.5 to 3 μm, and further preferably 1 to 3 μm. By making the film thickness of the second anodized titanium layer 22 greater than the above lower limit, it becomes easy to improve the voltage resistance and adhesion of the anodized titanium layer 20'. In addition, it is usually difficult to obtain a second anodized titanium layer 22 with a film thickness exceeding 5 μm. It should be noted that the film thickness of the second anodized titanium layer 22 can be measured by obtaining a scanning electron microscope image (SEM image) of a cross-section of the anodized titanium material perpendicular to the surface of the anodized titanium layer. The conditions for SEM observation when confirming the film thickness can be set, for example, to acceleration voltage: 15.0 kV, detection mode: reflected electron detection, magnification: 10,000 times.
[0109] The second anodized titanium layer 22 may or may not be porous, but is preferably porous. If the second anodized titanium layer 22 is porous, it is easy to increase the thickness of the second anodized titanium layer 22 and improve the withstand voltage of the anodized titanium layer 20'.
[0110] The fluorine content (unit: atomic %) in the second anodized titanium layer 22 is lower than the fluorine content (unit: atomic %) in the first anodized titanium layer 21. The fluorine content (unit: atomic %) in the first anodized titanium layer 21 and the second anodized titanium layer 22 can be measured by performing energy dispersive X-ray spectroscopy (EDS) measurement on the cross section of the anodized titanium material 200. The measurement conditions of EDS when measuring the fluorine content in each anodized titanium layer can be set to an acceleration voltage of 15.0 kV, for example. If the acceleration voltage is too high, the detection sensitivity to light elements such as oxygen and fluorine deteriorates. If the acceleration voltage is too low, the sensitivity to light elements becomes better. On the other hand, the detection sensitivity to heavy elements such as titanium deteriorates.
[0111] In the EDS measurement, the region where the electron beam incident on the titanium oxide is scattered in the titanium oxide and the characteristic X-rays are generated spans at least about 1 μm in diameter, for example, when the acceleration voltage is 15.0 kV. Therefore, if the film thickness of the second anodized titanium oxide layer 22 is sufficiently thick, the fluorine content (atomic %) of the second anodized titanium oxide layer 22 itself can be measured by EDS, but in the case where the film thickness of the second anodized titanium oxide layer 22 is thin (for example, the film thickness is 1 μm or less, etc.), even when the electron beam is incident on the second anodized titanium oxide layer 22, characteristic X-rays are generated not only from the second anodized titanium oxide layer 22 but also from the first anodized titanium oxide layer 21. Therefore, regardless of the fluorine content in the second anodized titanium oxide layer 22, characteristic X-rays originating from the F element in the first anodized titanium oxide layer 21 are generated, and as a result, it is sometimes difficult to measure the fluorine content of the second anodized titanium oxide layer 22 itself. However, even in such a case, by confirming that the measured value of the fluorine content when the electron beam is incident on the second anodized titanium oxide layer 22 in the EDS measurement is lower than the measured value of the fluorine content when the electron beam is incident on the first anodized titanium oxide layer 21, it can be confirmed that the fluorine content in the second anodized titanium oxide layer 22 is lower than the fluorine content in the first anodized titanium oxide layer 21.
[0112] It should be noted that, in the EDS measurement, the region where the electron beam incident on the titanium oxide is scattered in the titanium oxide to generate characteristic X-rays becomes narrower as the acceleration voltage is lowered. Therefore, when the film thickness of the second anodized titanium oxide layer 22 is thin, the acceleration voltage can be lowered, for example, to 5.0 kV, etc., in order to prevent the range where the characteristic X-rays are generated when the electron beam is incident on the second anodized titanium oxide layer 22 from including the titanium base material 10.
[0113] It should be noted that the inventors of the present invention conducted an actual analysis on one of the anodized titanium materials 200 (the film thickness of the second anodized titanium layer 22: about 2 μm) produced by the above-mentioned manufacturing method S200. As a result, the fluorine content measured by irradiating the first anodized titanium layer 21 with an electron beam (acceleration voltage 15.0 kV) on the cross section of the anodized titanium material was about 8 atomic %, while the fluorine content measured by irradiating the first anodized titanium layer 21 with an electron beam from the middle line between the first anodized titanium layer 21 and the titanium base material 10 in the second anodized titanium layer 22 was about 2 atomic %, and the fluorine content measured by irradiating the titanium base material 10 from the middle line in the second anodized titanium layer 22 with an electron beam was less than the detection limit (0.1 atomic %). Therefore, it can be considered that the fluorine content in the second anodized titanium layer 22 is actually less than the detection limit (0.1 atomic %) of the EDS measurement, and the second anodized titanium layer 22 is a layer that does not substantially contain fluorine.
[0114] It should be noted that the irradiation position of the electron beam when measuring the fluorine content in the first anodized titanium layer 21 by EDS is set to a position 3 to 5 μm away from the interface between the first anodized titanium layer 21 and the second anodized titanium layer 22 in the film thickness direction. This is because if in this area, the measured value will not be affected by the second anodized titanium layer 22, and the measured value is not easily affected by pores. The fluorine content of the first anodized titanium layer 21 measured by irradiating the electron beam to this area in the EDS measurement may also vary depending on the conditions of anodization and the composition of the electrolyte used, so it is difficult to stipulate in general terms, for example, it can be 1 to 20 atomic %.
[0115] According to the anodized titanium material 200 including the anodized titanium layer 20' including the second anodized titanium layer 22 in addition to the first anodized titanium layer 21, the adhesion between the anodized titanium layer 20' and the titanium base material 10 can be improved, and the withstand voltage of the anodized titanium layer 20' can be further improved.
[0116] Figure 6 FIG. 2 is a cross-sectional view schematically illustrating an anodized titanium material 300 according to another embodiment of the present invention. Figure 6 In, yes Figure 4-5 The element annotations shown in Figure 4-5 The same reference numerals as those in the reference numerals in the figure are omitted for explanation. The anodized titanium material 300 includes a metal base material 30 including a metal other than titanium in addition to the titanium base material 10 and the anodized titanium layer 20 described above. Furthermore, the titanium base material 10 is provided on the surface of the metal base material 30. Such an anodized titanium material 300 can be obtained, for example, by the anodized titanium material manufacturing method S100 described above in which the preparation step S10 includes a step of forming a titanium layer on the surface of a metal base material other than titanium.
[0117] Examples of the metal constituting the metal base material 30 include aluminum, stainless steel, and a combination thereof.
[0118] The stacking direction of the metal matrix 30, the titanium matrix 10 and the anodized titanium layer 20 (i.e. Figure 4 The lower limit of the thickness of the titanium base material 10 in the stacking direction is not particularly limited, and from the viewpoint of ease of manufacture, for example, it may be 0.1 μm or more, preferably 5 μm or more. The upper limit of the thickness of the titanium base material 10 in the stacking direction is not particularly limited, and from the viewpoint of ease of manufacture, for example, it may be 100 μm or less. In the case where the anodized titanium material 300 is obtained by the manufacturing method S100, the titanium of the titanium layer formed on the surface of the metal base material 30 in the preparation step S10 is oxidized, thereby growing the anodized titanium layer 20, and thus the thickness of the titanium base material 10 in the obtained anodized titanium material 300 becomes thinner than the titanium layer formed in the preparation step S10.
[0119] In the anodized titanium materials 100, 200, 300 of the present invention described above, the thermal expansion coefficient of the anodized titanium layer 20, 20' is close to that of the titanium base material 10, so even if exposed to a high temperature environment, the anodized titanium layer 20, 20' is not easy to crack. In addition, the anodized titanium layer 20, 20' has an improved voltage resistance, so it can be preferably used for applications where a high voltage is applied between the titanium base material 10 and the anodized titanium layer 20, 20' (for example, applications exposed to a plasma atmosphere, electrostatic chucks, etc.). In addition, the anodized titanium layer 20, 20' has sufficient hardness and surface smoothness, so it can also be preferably used as a component of a vacuum device that requires vacuum sealing. As a component of a vacuum device, that is, a component that requires vacuum sealing, for example, a component in a process chamber (process chamber) of a plasma etching device other than an electrostatic chuck (a lower electrode, a stand, an upper electrode, a cooling plate, a heating plate, etc., which are located below the chamber and the electrostatic chuck and apply a high-frequency voltage for generating plasma) can be listed. When aluminum having an oxide film on the surface is used as the material for the lower electrode, stand, etc. of conventional plasma etching devices, the durability of the device, especially under high and low temperature conditions, can be further improved by replacing them with the anodized titanium material of the present invention.
[0120] <Electrostatic chuck, cooling plate and shower head for plasma etching equipment>
[0121] Figure 7This is a cross-sectional view schematically illustrating an electrostatic chuck 100' for a plasma etching device according to an embodiment of the present invention (hereinafter, sometimes referred to as "electrostatic chuck 100'"), a cooling plate 4 for a plasma etching device according to an embodiment of the present invention (hereinafter, sometimes referred to as "cooling plate 4"), and a shower head 6 according to an embodiment of the present invention (hereinafter, sometimes referred to as "shower head 6"), as well as a plasma etching device 1000 having the electrostatic chuck 100', the cooling plate 4, and the shower head 6. Figure 7 In, yes Figures 4 to 6 The element annotations shown in Figures 4 to 6 The same reference numerals as those in the reference numerals in the figures are omitted from description. The plasma etching device 1000 is configured as a capacitively coupled parallel plate plasma etching device for etching a substrate 1 (e.g., a silicon wafer, etc.). The plasma etching device 1000 comprises: a chamber 2 formed into a square cylinder and made of aluminum having an anodized surface; a prismatic insulating plate 3 disposed at the bottom of the chamber 2 and made of an insulating material; a cooling plate (base) 4 disposed above the insulating plate 3; an insulating material 5 disposed on the outer periphery of the cooling plate 4; and an electrostatic chuck 100' disposed above the cooling plate 4.
[0122] The cooling plate (base) 4 includes: a conductive base substrate 4a; an insulating film 4b provided on the surface of the base substrate 4a; and a refrigerant flow path 4c provided inside the base substrate 4a. In the refrigerant flow path 4c, a refrigerant such as a fluorine-based liquid is introduced through a refrigerant introduction pipe 9a. The refrigerant introduced into the refrigerant flow path 4c removes heat from the base substrate 4a, flows out through a refrigerant recovery pipe 9b, is cooled by a condenser 9 provided outside the plasma etching device 1000, and is introduced into the refrigerant flow path 4c again through the refrigerant introduction pipe 9a.
[0123] The cooling plate (base) 4 comprises the anodized titanium material of the present invention, the base substrate 4a is a titanium base material (10), and the insulating film 4b provided on the surface of the base substrate 4a is an anodized titanium layer (20). As for the insulating film 4b as the anodized titanium layer, when a high-frequency voltage is applied to the adjacent base substrate 4a (titanium base material) by the high-frequency power supply 7 during the plasma etching process, since the insulating film 4b (anodized titanium layer) has an improved withstand voltage, the insulating film 4b is suppressed from being broken down even during the plasma etching.
[0124] A showerhead 6 is arranged above the cooling plate (base) 4, and the showerhead 6 is parallel to the cooling plate (base) 4 and functions as an upper electrode. The showerhead 6 is supported on the upper part of the chamber 2 and has a wall member 61 that defines an internal space 6a. The wall member 61 has at least a bottom surface 61a. The wall member 61 has: a gas inlet 6b for the processing gas for plasma etching to flow into the internal space 6a; and a plurality of gas exhaust holes 6c, 6c, ... (hereinafter, sometimes referred to as "gas exhaust holes 6c"), which are arranged on the bottom surface 61a for the processing gas to flow out from the internal space 6a. The showerhead 6 is grounded and forms a pair of parallel plate electrodes together with the base 4. The gas inlet 6b is connected to a processing gas supply source (not shown), and a processing gas for etching is supplied from the processing gas supply source (arrow A). There is no particular limitation as the processing gas, and a known gas such as a halogen gas, O2 gas, Ar gas, etc. can be used as a processing gas for plasma etching.
[0125] The shower head (upper electrode) 6 is provided with the anodized titanium material of the present invention, and the wall member 61 is formed of the anodized titanium material of the present invention. That is, the wall member 61 is provided with a titanium base material 61b (10) and an anodized titanium layer 61c (20) provided on the surface of the titanium base material 61b. The titanium base material 61b is grounded and functions as the electrode as described above. The anodized titanium layer 61c is exposed at least on the inner peripheral surface 6cw of each gas discharge hole 6c of the shower head 6.
[0126] Generally, it is difficult to provide a strong protective film such as a ceramic spray film on the inner peripheral surface of the gas discharge hole of the shower head for plasma etching apparatus, but the anodized titanium layer 61c functions as a protective film on the inner peripheral surface 6cw of the gas discharge hole 6c of the shower head 6. The anodized titanium material of the present invention has high heat resistance due to the small difference in thermal expansion coefficient between the titanium base material and the anodized titanium layer, so the generation of cracks in the anodized titanium layer is suppressed even under the conditions of plasma etching treatment. Therefore, according to the shower head 6, the inner peripheral surface 6cw of the gas discharge hole can be properly protected even under the conditions of plasma etching treatment.
[0127] The outer surface of the wall member 61 (for example, the bottom surface 61a as the plasma exposure surface) can be covered with a protective member made of single crystal silicon or quartz, for example, or can be covered with a ceramic spray film, etc. Preferred examples of ceramic materials covering the outer surface of the wall member 61 (for example, the bottom surface 61a) include plasma sprayed films of Al2O3, Y2O3, YF3, YAG (yttrium aluminum garnet), etc.
[0128] An exhaust port 2a is provided at the lower side wall of the chamber 2, and the exhaust port 2a is connected to an exhaust device (not shown). The exhaust device includes a vacuum pump such as a turbomolecular pump, and is configured to exhaust the atmosphere in the chamber 2 (arrow B) and reduce the pressure inside the chamber 2 to a predetermined pressure.
[0129] The susceptor base material 4a of the susceptor 4 is connected to the high-frequency power source 7 via the power supply line 7a. The high-frequency power source 7 supplies high-frequency power of, for example, 13.56 MHz to the susceptor 4.
[0130] The electrostatic chuck 100' is rectangular in plan view, and has the anodized titanium material 100 described above, which has a titanium base material 10 and an anodized titanium layer 20 provided on the surface of the titanium base material 10. The anodized titanium layer 20 is provided on the outermost surface of the electrostatic chuck 100'. The titanium base material 10 is connected to the DC power supply 8 via the power supply line 8a. In the electrostatic chuck 100', the titanium base material 10 acts as an electrode. By applying a DC voltage from the DC power supply 8 to the titanium base material 10 via the power supply line 8a, the substrate 1 can be electrostatically adsorbed to the surface of the electrostatic chuck 100', for example, by Coulomb force or Johnson-Rabbeck force. It should be noted that a through hole (not shown) is provided in the anodized titanium layer 20 at a portion located on the lower surface of the electrostatic chuck 100', and the power supply line 8a is wired through the through hole.
[0131] The processing operation of the plasma etching device 1000 is described. The substrate 1 as the object to be processed is carried into the chamber 2 through a substrate carrying port (not shown) provided on the side wall of the chamber 2 under the condition that the chamber 2 is at normal pressure, and is placed on the electrostatic chuck 100'. After that, the inside of the chamber 2 is depressurized to a predetermined vacuum degree by the exhaust device. After that, the processing gas is supplied from the processing gas supply source to the showerhead 6, and is uniformly discharged to the substrate 1 through the exhaust hole 6c, and the pressure in the chamber 2 is maintained at a predetermined value.
[0132] In this state, high-frequency power from the high-frequency power supply 7 is applied to the susceptor 4, thereby generating a high-frequency electric field between the susceptor 4 as the lower electrode and the showerhead 6 as the upper electrode. The processing gas is ionized and plasma-formed by the high-frequency electric field, and the generated plasma is used to perform etching processing on the substrate 1. During this period, a predetermined voltage is applied from the DC power supply 8 to the titanium base material 10 (electrode) of the electrostatic chuck 100', and the substrate 1 is adsorbed and held on the electrostatic chuck 100', for example, by Coulomb force. During the etching process, at least a portion of the anodized titanium layer 20 is exposed to the plasma atmosphere.
[0133] After the etching process is performed, the supply of high-frequency power from the high-frequency power source is stopped, the introduction of gas is stopped, and the pressure inside the chamber 2 is reduced to a predetermined value. Then, the inside of the chamber 2 is opened to normal pressure, and the substrate 1 is carried out to the outside of the chamber 2 through a substrate carrying port (not shown). As described above, the etching process of the substrate 1 is completed. In this way, the electrostatic chuck 100' can be used to carry out the etching process of the substrate 1 while holding the substrate 1 by electrostatic adsorption.
[0134] In the electrostatic chuck 100' of the present invention described above, the thermal expansion coefficient of the anodized titanium layer 20 is close to that of the titanium base material 10, so even if exposed to the high temperature environment of plasma etching, the anodized titanium layer 20 is not prone to cracking. In addition, during plasma etching, when a high voltage is applied between the titanium base material 10 and the anodized titanium layer 20, since the anodized titanium layer 20 has an improved voltage resistance, the anodized titanium layer 20 will not be insulated even during plasma etching. In addition, the anodized titanium layer 20 has sufficient hardness and surface smoothness, so sufficient vacuum sealing can be obtained, so that, for example, the lower surface of the substrate 1 can be prevented from being exposed to plasma.
[0135] Example
[0136] Hereinafter, the present invention will be described in further detail based on examples. However, the present invention is not limited to the following examples.
[0137] <Evaluation Method>
[0138] The evaluation methods in each of the Examples and Comparative Examples are as follows.
[0139] (Withstand voltage)
[0140] Using an insulation resistance meter IR4051 manufactured by Hioki Electric Co., Ltd., a DC voltage that was stepped up in the order of 50 V, 125 V, 250 V, 500 V, and 1000 V was applied between the base material and the surface of the anodized titanium layer, and the last applied voltage at which the anodized titanium layer did not undergo insulation breakdown was measured as the withstand voltage. When insulation breakdown did not occur even when a voltage of 1000 V was applied, the withstand voltage was set to "1000 V or more".
[0141] (Vickers hardness)
[0142] The Vickers hardness of the anodized titanium layer was measured using a micro Vickers hardness tester (Mitutoyo Co., Ltd. (formerly Akashi), HM-114). The measurement was performed in accordance with JIS Z2244, with a test load of 10 gf on the surface and the cross section.
[0143] (Surface smoothness)
[0144] The surface roughness (linear roughness) of the anodized titanium layer was measured using a high-precision surface roughness profile measuring instrument (Kosaka Laboratory, SE-30K). Based on the measurement results, the arithmetic mean roughness Ra and the maximum height roughness Rz were calculated in accordance with JIS B0601.
[0145] (film thickness)
[0146] The total film thickness of the anodized titanium layer was measured using an eddy current film thickness meter (Helmut Fischer, MP2 / O model).
[0147] (SEM observation)
[0148] A field emission scanning electron microscope (FE-SEM) (JEOL, JSM-7000F) was used to observe the surface and cross-sectional morphology. The conditions for SEM observation of cross-sectional morphology were set as accelerating voltage: 5.0 kV, detection mode: reflected electron detection, and magnifications: 1000, 2000, 10000, and 50000 times. In addition, the conditions for SEM observation of surface morphology were set as accelerating voltage: 10.0 kV, detection mode: secondary electron detection, and magnifications: 1000 and 4000 times. It should be noted that the samples for surface and cross-sectional observation were processed by flat milling using an ion milling device (JEOL, IB-09020CP).
[0149] (Adhesion)
[0150] The adhesion of the film was evaluated by a tape peeling test and an ultrasonic impact test. The tape peeling test was conducted in accordance with JIS H8504 (peeling test method: tape test method) to investigate whether the film peeled off. For the ultrasonic impact test, the sample was immersed in pure water (1L) in an ultrasonic tank (US-205 manufactured by SND), and ultrasonic waves with a frequency of 28kHz were irradiated for 30 minutes at an output power of 170W to investigate whether the film peeled off.
[0151] <Example 1>
[0152] The embodiment is as follows: a cold-rolled titanium plate (100 mm×50 mm×1 mm thick; surface roughness Ra (μm)=0.439, Rz (μm)=3.647) is used as a treated material, and an anodized titanium material manufacturing method S100 ( Figure 1 ) is anodized in a half area of 50 mm×50 mm, thereby producing an anodized titanium material 100 ( Figure 4 ).
[0153] The treated material was subjected to alkaline electrolytic degreasing and etching as pretreatment. The alkaline electrolytic degreasing was carried out by using an electrolyte obtained by diluting YUKEN Industries PAKUNA 171-N to a concentration of 50 g / L with deionized water, with the treated material as the anode and a current density of 50 mA / cm 2 The electrolysis was performed for 3 minutes. The etching was performed by immersing the material to be treated in an acidic ammonium fluoride aqueous solution (concentration 50 g / L) for 2 minutes.
[0154] After pretreatment, the treated material is anodized in the first electrolyte (step (b1)). The first electrolyte is prepared by dissolving acidic ammonium fluoride in a mixed solvent of ethylene glycol and pure water (mixed volume ratio 95:5) in a manner of 6 g / L. 5 L of the electrolyte is injected into a 5 L beaker (inner diameter 190 mm) as an electrolytic bath, and the temperature of the electrolyte is maintained at 5°C by a cooling device. The treated material is immersed in the electrolytic bath and used as an anode. The electrolyte is stirred at a certain speed by a magnetic stirrer at an electrolysis voltage of 130 V and an electrolysis current density of 10 mA / cm 2 During the electrolysis, the relative flow rate of the electrolyte to the treated material was maintained at 4 cm / sec.
[0155] After the electrolysis is completed, the treated material is taken out from the electrolytic bath, washed with ethanol and pure water, air-dried, and then further polished with a #4000 lapping film, thereby obtaining an anodized titanium material 100 .
[0156] The obtained anodized titanium layer had a thickness of 43 μm, a Vickers hardness of 260, a withstand voltage of 500 V or more at 25°C, and a surface roughness Ra of less than 1.6 μm (Ra = 0.469 μm, Rz = 4.144 μm). Although partial peeling was observed in the tape peeling test, a generally good anodized titanium material was obtained.
[0157] The cross-sectional SEM image of the obtained anodized titanium material (accelerating voltage 5.0 kV, reflected electron detection, magnification 1000 times) is shown in Figure 8 In addition, a surface SEM image (accelerating voltage 5.0 kV, reflected electron detection, magnification 10000 times) of the anodized titanium layer of the anodized titanium material is shown in Figure 8 In addition, a cross-sectional SEM image of the obtained anodized titanium material at a high magnification (accelerating voltage 5.0 kV, reflected electron detection, magnification 10000 times) is shown in Fig. 9 (A)~(C). Fig. 9 (A) is a cross-sectional SEM image of the surface of the anodized titanium layer. Fig. 9(C) is a cross-sectional SEM image of the interface between the anodized titanium layer and the titanium base material. Fig. 9 (B) is a cross-sectional SEM image of the anodized titanium layer near the center. Figure 8 The cross-sectional SEM image of (A) shows that there are no coarse voids in the first anodized titanium layer grown in step (b1), and no micro-arc oxidation occurs. Figure 8 The surface SEM image of (B) shows that no pore cross-section (opening) with a circular shape of 0.5 μm or more in diameter was observed on the surface of the first anodized titanium layer, and this surface SEM image also supports that micro-arc oxidation did not occur. Fig. 9 The cross-sectional SEM images of (A) to (C) can read out: the first anodized titanium oxide layer grown in process (b1) is porous throughout; the tubular pores in the first anodized titanium oxide layer grow approximately in the thickness direction; and there is a tendency that the tubular pores have a small pore diameter near the interface with the titanium base material and a large pore diameter near the surface layer.
[0158] It should be noted that in Figure 8 The surface SEM image of (B) shows the end of the structure having tubular pores. Figure 8 In the surface observed in (B), the portion where the tubular pores are not shown is covered by many plate-like fragments having a long dimension and a short dimension and having a curved surface in the short dimension. It can be considered that these curved plate-like fragments are produced by damage to the area near the end of the tubular structure. It can be considered that: in the anodized titanium material of the present invention, the tubular structure constituting the anodized titanium layer becomes larger as it approaches the surface layer, and the wall thickness of the wall portion decreases, so the portion that becomes brittle due to the reduction in wall thickness is damaged, thereby producing these fragments. As described later, these plate-like fragments can be removed by grinding.
[0159] The surface of the obtained anodized titanium material was polished by an ion milling device, and a surface SEM image of the cross section perpendicular to the thickness direction of the anodized titanium layer was obtained (accelerating voltage 5.0 kV, reflected electron detection, magnification 50000 times). The results are shown in Fig.10 (A) and Fig.10 (B). Fig.10 (A) is the SEM observation result of the obtained anodized titanium layer at a relatively shallow position from the surface. Fig.10 (B) is the SEM observation result of the obtained anodized titanium layer at a location relatively deep from the surface. Figure 8 The plate-like fragments observed in the surface SEM image of (B) were removed. Figure 8 (B) Fig.10 (A) and Fig.10(B) shows that the structure having tubular pores constituting the anodized titanium layer has a smaller pore diameter and a thicker wall thickness as it approaches the titanium base material side, and a larger pore diameter and a thinner wall thickness as it approaches the surface layer side.
[0160] <Example 2>
[0161] The anodized titanium material of the present invention was produced in the same manner as in Example 1 except that the electrolysis time of the anodization in step (b1) was changed to 60 minutes. The obtained anodized titanium layer had a film thickness of 25 μm, a Vickers hardness of 260, a withstand voltage of 500 V or more at 25° C., and a surface roughness Ra of less than 1.6 μm (Ra=0.644 μm, Rz=4.144 μm). No peeling was observed in the tape peeling test.
[0162] <Comparative Example 1>
[0163] This comparative example is as follows: Production of an anodized titanium material was attempted in the same manner as in Example 1 except that the temperature of the first electrolyte solution in step (b1) was changed to 25°C.
[0164] The obtained anodized titanium layer had a film thickness of less than 20 μm, a Vickers hardness of 160, a withstand voltage of 250 V, and a surface roughness Ra of less than 1.6 μm. No peeling was observed in a tape peeling test.
[0165] The cross-sectional SEM image of the obtained anodized titanium material (accelerating voltage 5.0 kV, reflected electron detection, magnification 1000 times) is shown in Fig.11 .according to Fig.11 It can be read that there are no coarse voids with a pore width of more than 1 μm in the surface direction in the first anodized titanium layer, and micro-arc oxidation has not occurred. Fig.11 and Figure 8 When compared with (A), it can be seen that the film thickness of the anodized titanium layer obtained in Comparative Example 1 is significantly thinner than the film thickness of the anodized titanium layer obtained in Example 1.
[0166] <Comparative Example 2>
[0167] This comparative example is as follows: Production of an anodized titanium material was attempted in the same manner as in Example 1 except that the relative flow rate of the electrolyte solution to the material to be treated in step (b1) was changed to 0.8 cm / sec.
[0168] The obtained film was very thin, so the film thickness could not be measured by an eddy current film thickness meter, and the Vickers hardness could not be measured. The withstand voltage was 50 V, and the surface roughness Ra was less than 1.6 μm. The film peeled off in the tape peeling test.
[0169] <Comparative Example 3>
[0170] The production of an anodized titanium material was attempted in the same manner as in Example 1, except that the relative flow rate of the electrolyte solution to the material to be treated in the step (b1) was changed to 5.65 cm / sec.
[0171] The obtained anodized titanium layer had a film thickness of less than 20 μm, a Vickers hardness of 250, a withstand voltage of 250 V, and a surface roughness Ra of less than 1.6 μm. Partial peeling was observed in the tape peeling test.
[0172] <Comparative Example 4>
[0173] In step (b1), the electrolysis conditions were changed to conditions that allow micro-arc oxidation (plasma electrolytic oxidation) to occur (electrolyte: phosphoric acid-sulfuric acid aqueous solution (sulfuric acid 1.5 mol / L, phosphoric acid 0.3 mol / L), electrolysis voltage: 300 V, electrolysis current density: 10 mA / cm 2 , electrolysis time: 30 minutes), except for this, the production of anodized titanium material was attempted in the same manner as in Example 1.
[0174] The film thickness of the obtained anodized titanium layer was less than 5 μm, which was too thin to measure the Vickers hardness. The withstand voltage was 250 V, and the surface roughness Ra was not less than 1.6 μm. No peeling was observed in the tape peeling test.
[0175] The cross-sectional SEM image (accelerating voltage 5.0 kV, reflected electron detection, magnification 10000 times) and surface SEM image (accelerating voltage 5.0 kV, reflected electron detection, magnification 10000 times) of the obtained anodized titanium material are shown in Fig.12 (A) and Fig.12 (B). According to Fig.12 (A) shows that the anodized titanium layer obtained in Comparative Example 4 is not only thicker than the anodized titanium layer obtained in Example 1 (reference Figure 8 The (A)) is thin and has coarse voids with a pore width of more than 1 μm in the surface direction. Micro-arc oxidation occurs during electrolysis. The effect of micro-arc oxidation on the voids is roughly isotropic in the surface direction, so it can be considered that Fig.12 The coarse voids observed in the cross-sectional SEM image of (A) have the same depth in the width direction. Figure 8 (A) and Fig. 9 ). The surface roughness is also significantly worse than that of (A). Fig.12 In the surface SEM image of (B), a pore cross section (opening) having a shape that can include a circle with a diameter of 0.5 μm or more appears. From this, it can be understood that coarse voids are formed by micro-arc oxidation.
[0176] <Comparative Example 5>
[0177] This comparative example is a comparative example of producing an aluminum anodized film for comparison. According to JIS H8601, an Al-Mg-Si aluminum alloy (A6061) plate is anodized in a sulfuric acid bath to produce a sulfuric acid-resistant aluminum film (film thickness 50μm) on the surface of the plate. The withstand voltage (insulation breakdown voltage) of the sulfuric acid-resistant aluminum film at 25°C is 1602V.
[0178] <Comparative Example 6>
[0179] This comparative example is a comparative example of producing an aluminum anodized film for comparison. According to JIS H8601, an Al-Mg-Si aluminum alloy (A6061) plate is anodized in an oxalic acid bath to produce an oxalic acid-resistant aluminum film (film thickness 24μm) on the surface of the plate. The withstand voltage (insulation breakdown voltage) of the oxalic acid-resistant aluminum film at 25°C is 1027V.
[0180] <Temperature dependence of withstand voltage>
[0181] The temperature dependence of the withstand voltage of the anodized titanium layer was evaluated for the anodized titanium materials produced in Examples 1 and 2. The withstand voltage was measured 3 to 8 times at various temperatures using an insulator voltage tester (voltage increase rate 100 V / s) in accordance with JIS H8687, and the average value was calculated. The results are shown in Fig.13 . Fig.13 (A) is a graph showing the results of measuring the withstand voltage of the anodized titanium layer obtained in Example 1 according to the temperature of the anodized titanium material. Fig.13 (B) is a graph showing the results of measuring the withstand voltage of the anodized titanium layer obtained in Example 2 according to the temperature of the anodized titanium material. Fig.13 (A) and Fig.13 In the graph of (B), the error bar is the standard error of the measured value. Fig.13 (A) and Fig.13 (B) shows that: (1) the thicker the anodized titanium layer, the higher the withstand voltage becomes; and (2) the withstand voltage is lowest near room temperature (25°C), and the withstand voltage increases regardless of whether the temperature is increased or decreased from room temperature. It should be noted that the withstand voltage at each temperature was measured multiple times on the same sample, but it is noted that the change in withstand voltage caused by temperature change is roughly reversible.
[0182] The temperature dependence of the withstand voltage was also evaluated for the anodized aluminum films produced in Comparative Examples 5 and 6. The results are shown together with the results of Examples 1 and 2. Fig.14 It should be noted that Fig.14 The vertical axis of the graph is the withstand voltage per unit film thickness (V / μm). Fig.14As can be seen, the withstand voltage of the anodized aluminum films produced in Comparative Examples 5 and 6 decreases when the temperature is raised from 25° C. to 120° C. The decrease in withstand voltage caused by exposing the anodized aluminum film to high temperature is generally irreversible.
[0183] The anodic oxide film (aluminum film) formed on the aluminum base material, represented by oxalate aluminum and sulfate aluminum, will crack at high temperatures such as 150°C due to the difference in thermal expansion coefficient between the aluminum base material and the anodic oxide film (aluminum film), and the withstand voltage will decrease. Therefore, the reduction in withstand voltage is irreversible, and even if the aluminum film is restored to room temperature, the withstand voltage reduced by exposing the aluminum film to high temperature will not be restored. Fig.14 The withstand voltage of the anodized aluminum films of Comparative Examples 5 and 6 has already decreased at 120° C. Therefore, conventional aluminum anodized films cannot be used in locations that are repeatedly exposed to a thermal budget such as high temperatures of 150° C. and low temperatures of −50° C.
[0184] In contrast, the anodized titanium layer of the anodized titanium material of the present invention has the following unique properties: (1) the withstand voltage is lowest near room temperature (25°C), and the withstand voltage increases regardless of whether the temperature is increased or decreased from room temperature; and (2) the change in withstand voltage caused by temperature change is reversible. Therefore, the anodized titanium material of the present invention can be particularly preferably used for components that require electrical insulation and are repeatedly exposed to heat.
[0185] <Example 3>
[0186] The embodiment is as follows: The same cold-rolled titanium plate as in embodiment 1 (100 mm×50 mm×1 mm thick; surface roughness Ra (μm)=0.439, Rz (μm)=3.647) is used as a treated material, and the anodized titanium material manufacturing method S200 ( Figure 2 ) is anodized in a half area of 50 mm × 50 mm, thereby producing an anodized titanium material 200 ( Figure 5 ).
[0187] The material to be treated was subjected to alkaline electrolytic degreasing and etching as pretreatment in the same manner as in Example 1.
[0188] After pretreatment, the treated material is anodized in the first electrolyte (step (b1)). The first electrolyte is prepared by dissolving acidic ammonium fluoride in a mixed solvent of ethylene glycol and pure water (mixing volume ratio 95:5) in a manner to a concentration of 6 g / L. 5 L of the first electrolyte is injected into a 5L beaker (inner diameter 190 mm) as an electrolytic bath, and the temperature of the electrolyte is maintained at 5°C by a cooling device. The treated material is immersed in the electrolytic bath and used as an anode. The electrolyte is stirred at a certain speed by a magnetic stirrer, and the electrolysis voltage is 130 V and the electrolysis current density is 10 mA / cm2 During the electrolysis, the relative flow rate of the electrolyte to the treated material was maintained at 4 cm / sec.
[0189] After the electrolysis of step (b1) is completed, the treated material is further anodized in the second electrolyte (step (b2)). A mixed solution of ethylene glycol, pure water and 30% hydrogen peroxide solution (mixing volume ratio: 90:50:5) is used as the second electrolyte. 5L of the second electrolyte is injected into a 5L beaker (inner diameter 190mm) as an electrolytic bath, and the temperature of the electrolyte is maintained at 10°C by a cooling device. The treated material after the electrolysis of step (b1) is not washed, and is immersed in the electrolytic bath as an anode. The electrolyte is stirred at a certain speed by a magnetic stirrer, and the electrolysis voltage is 100V and the electrolysis current density is 10mA / cm 2 During the electrolysis, the relative flow rate of the electrolyte to the treated material was maintained at 4 cm / sec.
[0190] After the electrolysis in step (b2) is completed, the material to be treated is taken out from the electrolytic bath, washed with ethanol and pure water, and air-dried, thereby obtaining an anodized titanium material 200.
[0191] The obtained anodized titanium layer has a film thickness of 50 μm or more, a Vickers hardness of 250 or more, a withstand voltage of 1000 V or more, and a surface roughness Ra of less than 1.6 μm (Ra = 1.072 μm, Rz = 5.882 μm). No peeling was observed in either the tape peeling test or the ultrasonic impact test, and a film with very high adhesion was obtained.
[0192] The cross-sectional SEM image of the obtained anodized titanium material is shown in Fig.15 (A) and Fig.15 (B) shows the surface SEM image of Fig.16 . Fig.15 (A) is a cross-sectional SEM image of the entire anodized titanium layer (accelerating voltage 15.0 kV, reflected electron detection, magnification 2000 times), Fig.15 (B) is a cross-sectional SEM image of the interface between the anodized titanium layer and the titanium base material (accelerating voltage 15.0 kV, reflected electron detection, magnification 10000 times). Fig.15 (A) and Fig.15 (B) shows that: there are no large voids in the first anodized titanium layer; and there is a second anodized titanium layer with a thickness of about 2 μm grown in step (b2) between the first anodized titanium layer grown in step (b1) and the titanium base material. Fig.15(B) can be read as follows: the second anodized titanium oxide layer has a porous structure influenced by the first anodized titanium oxide layer. Fig.16 This is a surface SEM image of the anodized titanium layer (accelerating voltage 5.0 kV, reflected electron detection, magnification 40,000 times). Fig.16 In the figure, the ends of the tubular pores extending in the thickness direction of the anodized titanium layer are shown. Fig.16 It was read that the diameter of each tubular pore was 0.3 μm or less, and that no pore cross section (opening) having a shape including a circle having a diameter of 0.5 μm or more was observed.
[0193] The film composition of the anodized titanium material obtained in Example 3 was evaluated by EDS measurement using an energy dispersive X-ray spectrometer (JEOL, JED2000). The acceleration voltage was set to 15.0 kV. Fig.17 In the cross-sectional SEM image, the numbers 1 to 12 represent the locations where the composition was measured (locations irradiated with electron beams in EDS measurement). Measurement locations 1, 4, and 7 are the first anodized titanium layer, measurement locations 2, 5, 8, 10 to 12 are the second anodized titanium layer, and measurement locations 3, 6, and 9 are titanium base materials. It should be noted that measurement locations 1, 4, and 7 are about 4 μm from the interface between the first anodized titanium layer and the second anodized titanium layer. The measurement results of the composition in each measurement location are shown in Table 1.
[0194] (Table 1)
[0195]
[0196] According to the SEM observation of the cross section, it can be seen that the film thickness of the second anodized titanium layer is about 2μm. In the EDS measurement, the fluorine content measured by irradiating the first anodized titanium layer with an electron beam (acceleration voltage 15.0kV) is about 8 atomic% (measurement sites 1, 4, and 7). In contrast, the fluorine content measured by irradiating the second anodized titanium layer from the middle line between the first anodized titanium layer and the titanium base material to the first anodized titanium layer side is about 2 atomic% (measurement sites 2, 5, and 8). In addition, the fluorine content measured by irradiating the second anodized titanium layer from the above-mentioned middle line to the titanium base material side is less than the detection limit (0.1 atomic%) (measurement sites 10 to 12). It can be seen from this that the titanium content (atomic%) of the second anodized titanium layer is lower than the titanium content (atomic%) of the first anodized titanium layer. It can be further considered that the fluorine content in the second anodized titanium layer is actually less than the detection limit (0.1 atomic%) of the EDS measurement, and the second anodized titanium layer is a layer that does not substantially contain fluorine.
[0197] <Expansion and contraction characteristics of anodized titanium layer due to temperature changes>
[0198] The cross section of the anodized titanium layer obtained in Example 3 was observed by SEM while changing the temperature (accelerating voltage 5.0 kV, reflected electron detection, magnification 2200 times). After SEM observation was first performed at room temperature (26°C), the sample temperature was raised to 150°C and SEM observation was performed. Thereafter, the sample was opened to the atmosphere and the sample temperature was restored to room temperature (26°C), and then SEM observation was performed again. The sample temperature was adjusted during SEM observation using a heating stage (Gatan, Muranoheating stage). In addition, only the anodized titanium layer was separated from the anodized titanium material of Example 3 using an ion milling device (JEOL, IB-09020CP). The surface of the surface layer side and the surface of the base material side of the separated anodized titanium layer were observed by SEM while changing the temperature in the same manner as described above (accelerating voltage 5.0 kV, reflected electron detection, magnification 40000 times). The results are shown in Fig.18 .exist Fig.18 In the figure, the left column (A)(D)(G) is the SEM image at the initial room temperature (26°C), the middle column (B)(E)(H) is the SEM image at 150°C, and the right column (C)(F)(I) is the SEM image when the sample temperature is restored to room temperature (26°C). The upper row (A)(B)(C) is the SEM image of the surface of the surface side of the anodized titanium oxide layer, the middle row (D)(E)(F) is the SEM image of the surface of the base material side of the anodized titanium oxide layer, and the lower row (G)(H)(I) is the cross-sectional SEM image of the anodized titanium oxide layer. When the temperature is raised from room temperature to 150°C, the anodized titanium oxide layer shrinks by approximately 3% in the length dimension in the plane direction on the surface side ((A)→(B)), shrinks by approximately 2% in the length dimension in the plane direction on the base material side ((D)→(E)), shrinks by approximately 2.5% in the length dimension in the plane direction approximately in the middle portion between the surface side and the base material side ((G)→(H)), and shrinks by approximately 1% in the length dimension in the thickness direction ((G)→(H)). When cooled from 150°C to room temperature, the anodized titanium layer shrinks by about 8% in the plane direction in terms of length on the surface side ((B)→(C)), but expands by about 2% in the plane direction in terms of length on the base material side ((E)→(F)), expands by about 1% in the plane direction in terms of length in the roughly middle portion between the surface side and the base material side ((H)→(I)), and expands by about 0.5% in the thickness direction in terms of length ((H)→(I)). Although this is not meant to be limited by theory, it can be considered that: in this way, the pore structure of the anodized titanium layer shrinks as the temperature rises, which leads to an increase in withstand voltage as the temperature rises. In addition, it can be considered that: the pore structure expands and contracts roughly reversibly except for the surface portion, which leads to a roughly reversible change in withstand voltage caused by temperature changes.
[0199] Description of Reference Numerals
[0200] 1: substrate; 2: chamber; 3: insulating plate; 4: cooling plate (base); 5: insulating material; 6: nozzle (upper electrode); 7: high-frequency power supply; 8: direct current power supply; 10: titanium base material; 20, 20': anodized titanium layer; 21: first anodized titanium layer; 22: second anodized titanium layer; 30: metal base material (other than titanium); 100, 200: anodized titanium material; 100': electrostatic chuck; 1000: plasma etching device.
Claims
1. An anodized titanium material, characterized in that: have: Titanium parent metal; and an anodic titanium oxide layer provided on the surface of the titanium base material, The anodized titanium layer includes a porous first anodized titanium layer. The anodized titanium layer has a withstand voltage of 500 V or more at 25° C., a Vickers hardness of 200 or more, a film thickness of 20 μm or more and less than 80 μm, a surface arithmetic mean roughness Ra of less than 1.6 μm, and a surface maximum height roughness Rz of less than 6.3 μm. The first anodized titanium oxide layer has a plurality of tubular pores, and the tubular pores extend in a direction intersecting the surface of the anodized titanium oxide layer. In neither the cross section perpendicular to the thickness direction nor the surface of the first anodized titanium oxide layer is a pore cross section having a shape that can include a circle having a diameter of 0.5 μm or more observed, The anodized titanium material is obtained by anodizing a material having titanium on its surface using a first electrolyte having a temperature below 10°C, an electrolysis voltage below 200V, and a relative flow rate of the first electrolyte relative to the material being treated of not less than 1 cm / second and not more than 5 cm / second.
2. The anodized titanium material according to claim 1, wherein: The withstand voltage of the anodized titanium layer at 150° C. is higher than the withstand voltage at 25° C.
3. The anodized titanium material according to claim 1 or 2, wherein: The anodized titanium layer further includes a second anodized titanium layer disposed between the titanium matrix and the first anodized titanium layer. The fluorine content in the second anodized titanium layer is lower than the fluorine content in the first anodized titanium layer, wherein the unit of the fluorine content is atomic %.
4. The anodized titanium material according to claim 1 or 2, wherein: further comprising a metal base material including a metal other than titanium, The titanium matrix is arranged on the surface of the metal matrix.
5. The anodized titanium material according to claim 1 or 2, wherein: The anodized titanium material is a component of a vacuum device, and is used as a component for exposing the anodized titanium layer to a plasma atmosphere.
6. An electrostatic chuck for a plasma etching device, which is an electrostatic chuck for a plasma etching device, and the electrostatic chuck for a plasma etching device comprises: The anodized titanium material according to claim 1 or 2, The anodized titanium layer is disposed on the outermost surface of the electrostatic chuck and is exposed to a plasma atmosphere.
7. A cooling plate for a plasma etching device, which is a cooling plate for a plasma etching device, the cooling plate for a plasma etching device comprising: The anodized titanium material according to claim 1 or 2; and A refrigerant flow path is provided inside the cooling plate to allow the refrigerant to flow. The anodized titanium layer is disposed on the outermost surface of the cooling plate.
8. A shower head for a plasma etching device, which is a shower head for a plasma etching device, the shower head for a plasma etching device comprising a wall member, the wall member comprising the anodized titanium material according to claim 1 or 2, defining an internal space, The wall member has at least a bottom surface, The wall member comprises: A gas inlet port allows a plasma etching processing gas to flow into the internal space; and A plurality of gas exhaust holes are provided on the bottom surface to allow the processing gas to flow out from the internal space. The anodized titanium layer is exposed at least on the inner peripheral surfaces of the plurality of gas discharge holes.
9. A method for manufacturing anodized titanium material, characterized in that: The method for manufacturing an anodized titanium material according to claim 1, comprising: Step (a), preparing a material to be treated having titanium on its surface; and Step (b), anodizing the material to be treated, The step (b) comprises a step (b1) of anodizing the material to be treated in a first electrolyte solution. In the step (b1), The first electrolyte comprises a non-aqueous solvent that can be uniformly mixed with water and a fluoride ion source, and further comprises water or does not contain water. The temperature of the first electrolyte is below 10°C, The electrolysis voltage is below 200V. A relative flow rate of the first electrolyte solution with respect to the material to be treated is 1 cm / sec or more and 5 cm / sec or less.
10. The method for manufacturing anodized titanium material according to claim 9, wherein: The first electrolyte comprises: 88-97 mass % of ethylene glycol as the non-aqueous solvent based on the total amount of the electrolyte; 1 to 10% by mass of water based on the total amount of the electrolyte; and The fluoride ion source is present in an amount of 2000 to 5000 ppm by mass in terms of fluorine atoms based on the total amount of the electrolyte.
11. The method for producing an anodized titanium material according to claim 9 or 10, wherein: The step (b) further comprises a step (b2) of anodizing the material to be treated after the step (b1) in a second electrolyte having a fluoride ion source concentration of 10 ppm by mass or less in terms of fluorine atoms. In the step (b2), The temperature of the second electrolyte is below 70°C, The electrolysis voltage is below 200V. A relative flow rate of the second electrolyte solution with respect to the material to be treated is 1 cm / sec or more and 5 cm / sec or less.
12. The method for producing an anodized titanium material according to claim 11, wherein: The second electrolyte comprises: 89.9 to 99.6 mass % of ethylene glycol based on the total amount of the electrolyte; 0.1 to 3% by mass of hydrogen peroxide based on the total amount of the electrolyte; and 0.3 to 10% by mass of water based on the total amount of the electrolyte.
13. The method for producing an anodized titanium material according to claim 9 or 10, wherein: The step (a) includes the step of forming a titanium layer on the surface of a metal base material other than titanium.
14. The method for producing an anodized titanium material according to claim 9 or 10, wherein: The method further comprises a step (c) of polishing the surface of the anodized titanium layer formed in the step (b).
Citation Information
Patent Citations
Electrostatic chuck, plasma processing apparatus, and plasma processing method
JP2005136350A
Electrostatic attraction electrode, substrate processor, and manufacturing method for electrostatic attraction electrode
JP2008066707A
Plasma etching device
JP2014053481A
High purity metallic top coat for semiconductor manufacturing components
CN105723503A
Anodic oxidation of magnetic disk substrate made of titanium
JP1994236548A